2008
DOI: 10.1007/s00441-007-0555-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tissue-harvesting site on yield of stem cells derived from adipose tissue: implications for cell-based therapies

Abstract: The stromal vascular fraction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
231
4
14

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(273 citation statements)
references
References 43 publications
17
231
4
14
Order By: Relevance
“…After isolation of the ASCs from the SVF, we also found that the outer thigh region contained higher concentration of ASCs, compared to the abdomen, waist and the inner knee. This is in contrast to a previous study in which the abdomen has appeared as a preferable region for harvesting adipose tissue due to the higher ASCs yield (8).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…After isolation of the ASCs from the SVF, we also found that the outer thigh region contained higher concentration of ASCs, compared to the abdomen, waist and the inner knee. This is in contrast to a previous study in which the abdomen has appeared as a preferable region for harvesting adipose tissue due to the higher ASCs yield (8).…”
Section: Discussioncontrasting
confidence: 87%
“…In particular, preclinical studies have revealed their capacity to differentiate toward the osteogenic, adipogenic, myogenic, and chondrogenic lineages (6,7). Nevertheless, adipose tissue displays a significant heterogeneity in terms of stem cell yield, proliferation, and differentiation capacity not only among individuals, but even when comparing different fat depots within one individual (8).…”
Section: Thigh Showed a Significantly Higher Number Of Ascs Compared mentioning
confidence: 99%
“…To exclude that stimulation with 5-aza-2-deoxycitidine also triggered the differentiation of ASC towards other lineages, we also tested our samples for markers for osteogenic and chondrogenic lineages at 5 weeks after treatment, as described previously (Jurgens et al 2008). No expression of the chondrogenic marker collagen type 2b was found in any of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Jurgens et al [ 46 ] have recently demonstrated that not only differences exist among individuals, but also yield and functional features of hASCs are affected by the adipose tissue-harvesting site.…”
Section: Discussionmentioning
confidence: 99%